INDIVIDUAL VARIATIONS IN MONITOR HYPOTHESIS OF MICRO TEACHING STUDENTS - Gregoriana Nobilio Pasia Janu (UC Journal: ELT, Linguistics and Literature Journal, 2020)
The paper aims to find out the types of users in performing English as a second language and to figure out principal conditions that might affect students monitoring process as proposed by Krashen (1982). Two research problems were formulated, namely: First, what individual variations are shown by students in the Micro Teaching class? Second, to what extent do Micro teaching students regard the three principal conditions in the monitor hypothesis? Both qualitative and quantitative methods were used. The qualitative method of data collection was participant observation. Nineteen students Micro Teaching videos were recorded to be observed to answer the first research problem. The quantitative method was applied through a questionnaire to answer the second research problem. An interview was also done to support the analysis of the questionnaire. The results showed that only two types of monitor users occurred in Micro Teaching Class A. The two types were monitor under-users, who were not aware of the conscious checking, and monitor over-users, who seemed to consciously check their L2 output.